Is War Still a Scourge? Ukraine and the international legal (Dis)order - Baccelli, Luca (Soft Power, 2024)
Nothing will be like before, again? In ‘the West’ the media coverage of the War on Ukraine and mainstream public opinion leave us such a feeling. We are supposed to see a previously unknown break in the international order, an attack on liberal democracies by the Russian authoritarian regime. On the other side, Putin’s propaganda openly speaks of the conflict commitment of the broader West and the NATO. Then, of course, there is the rest of the World. On March 2nd, 2022, the UN General Assembly “overwhelmingly” adopted a resolution demanding the “unconditional withdraw” of Russian army from Ukraine. But among the 35 abstentions there were countries like China, India, in an unusual agreement with Pakistan, Iran, South Africa. On April 8th China together with other 23 countries voted against the resolution calling for Russia to be suspended from the Human Rights Council; the 48 abstentions including Brazil, Mexico, Egypt, Saudi Arabia, Malaysia and Indonesia. The governments which represents the majority of humankind do not share the “Western” point of view. It would be easy to stress the authoritarian character of most of those governments, but it would be an error to underestimate the widespread – e.g., in Africa – latent hostility against “us” and the impatience against “our” double standards for what concerns aggressions and humanitarian emergencies.